Pengaruh Jumlah Uang Beredar terhadap Pertumbuhan Ekonomi melalui Investasi sebagai Variabel Intervening pada Provinsi Sumatera Utara - Sari, Arsiska; Syahbana, Eza; Alisya, Jeane; Batubara, Radja Marihat; Marbun, Jonatan; Silaban, Putri Sari Margaret Julianty (Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes the impact of money supply on economic growth with investment as an intervening variable in North Sumatra during the 2010-2023 period. Using path analysis and secondary data from BPS and Bank Indonesia, the results show that money supply significantly affects economic growth (probability 0.0004) and investment (t-statistic 5.701674; probability 0.0001). Investment also significantly influences economic growth (probability 0.0385) and mediates the relationship between money supply and economic growth (Sobel test, 2.1726; probability 0.0298). The coefficient of determination indicates that 94.4% of the variation in economic growth is explained by money supply and investment. These findings support Keynesian and Harrod-Domar theories on the importance of liquidity and investment. The study recommends integrated monetary and investment policies to support sustainable economic growth in North Sumatra.